2019
DOI: 10.5430/ijfr.v10n3p239
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Enterprise Risk Management and Firm Performance in Malaysia

Abstract: This study aims to examine the relationship between enterprise risk management (ERM) implementation and firm performance in Malaysia. Using the sample from 2010 to 2016, this study examines the relationship between ERM and firm performance among Malaysian top 100 public listed firms registered on the Index FTSE Bursa Malaysia 100 (FBM100) KLSE. This study also provides comparisons before and after the introduction of Bursa Malaysia Guidelines 2013. This study shows a positive and significant coefficient betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…So it can be concluded that leverage has a negative and significant effect on firm value. The results of this study are in line with Agustina (2017), Rahmadani and Rahayu (2017), Horvey and Ankamah (2020), Ali et al (2019), and Gustian (2017) which states that Leverage has a negative effect on firm value. This is due to the higher the level of debt owned by the company, the higher the interest expense paid by the company so that the company's ability to generate profits will decrease.…”
Section: The Effect Of Leverage On Firm Valuesupporting
confidence: 89%
See 1 more Smart Citation
“…So it can be concluded that leverage has a negative and significant effect on firm value. The results of this study are in line with Agustina (2017), Rahmadani and Rahayu (2017), Horvey and Ankamah (2020), Ali et al (2019), and Gustian (2017) which states that Leverage has a negative effect on firm value. This is due to the higher the level of debt owned by the company, the higher the interest expense paid by the company so that the company's ability to generate profits will decrease.…”
Section: The Effect Of Leverage On Firm Valuesupporting
confidence: 89%
“…While Figures 1.1 and 1.5 show the phenomenon that ERM disclosure has a pattern that tends to be in line with firm value. This is not in line with the research of Aditya and Naomi (2017) and Ali et al (2019) which states that the implementation of ERM has a negative effect on firm value.…”
Section: Figure 5 Graph Of Financial Sector Erm Disclosures For 2015-...contrasting
confidence: 83%
“…The methodology has been modified and applied to the non-financial sector over the years (Otero González et al 2020). Authors of empirical research who have used content analysis have mostly selected a core set of listed companies, financial institutions, or insurance companies (Tahir and Razali 2011;Lin et al 2012;Khan et al 2016;Kommunuri et al 2016;Abdullah et al 2018;Iswajuni et al 2018;Lechner and Gatzert 2018;Zou et al 2018;Ali et al 2019;Jonek-Kowalska 2019;Silva et al 2019;Otero González et al 2020). These companies are required to disclose information about their risk management practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The relationship between ERM and company performance is introduce (Soltanizadeh et al, 2016); ; (Ali et al, 2019); (Shad et al, 2019) and (Nasr et al, 2019). Results study of (Annamalah et al, 2018) is a significant and positive relationship between ERM and business performance.…”
Section: Introductionmentioning
confidence: 99%
“…ERM is a fundamental and comprehensive model that has evolved from a traditional system, a holistic and integrated system (Nasr et al, 2019). This can provide a greater awareness of the company about the risks that increase and the company's ability to respond to risk effectively, thereby increasing the efficiency and effectiveness of the company's operations (Ali et al, 2019).…”
Section: Introductionmentioning
confidence: 99%